Are You Listening ? The Sense of Hearing - Maule, David (NewYork Cambridge University, 2014)
What do you really know about the sense of hearing? Learn all about the science of sound, the crazy noises animals make, and the loudest and quietest places on Earth.
Cambridge Discovery Education Interactive Readers are the next generation of graded readers - captivating topics, high-impact video, and interactive exercises designed to motivate and engage.
Glossary, Contents.
Keywords: English language; Elementary level